2017
DOI: 10.26719/2017.23.7.500
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of patients with asthma: a cross-sectional study in Semnan, Islamic Republic of Iran

Abstract: Qualité de vie liée à la santé de patients asthmatiques : étude transversale à Semnan, République islamique d'IranRÉSUMÉ L'asthme peut affecter gravement la qualité de vie des personnes qui en souffrent. Les données sur la qualité de vie des personnes vivant avec l'asthme en République islamique d'Iran sont en nombre limité. La présente étude transversale avait pour objectif d'évaluer la qualité de vie des adultes asthmatiques à Semnan sur la base du SF-36, un questionnaire court d'enquête sur la santé compren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Asthma patients experience several limitations in their daily activities, productivity, physical and emotional capacity [ 1 , 2 , 6 , 11 ], and especially sleep quality [ 4 , 12 , 13 ]. QoL in asthmatic patients is affected by several factors, such as gender, socioeconomic status, education level, and place of residence [ 3 , 9 , 14 ]. Numerous studies have shown that QoL indices have significant determining effects on the classification, diagnosis, and treatment of asthmatic patients [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma patients experience several limitations in their daily activities, productivity, physical and emotional capacity [ 1 , 2 , 6 , 11 ], and especially sleep quality [ 4 , 12 , 13 ]. QoL in asthmatic patients is affected by several factors, such as gender, socioeconomic status, education level, and place of residence [ 3 , 9 , 14 ]. Numerous studies have shown that QoL indices have significant determining effects on the classification, diagnosis, and treatment of asthmatic patients [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These observations can be confirmed if we compare health status of Iranian subjects with diabetes with the health status of people with chronic-degenerative disorders, such as rheumatoid arthritis with an average score of 52.47 [ 55 ], or cardiovascular disorders with a mean of 53.19 [ 56 ], among others. Similarly, low scores have been found for asthma [ 57 ] or chronic kidney disease [ 58 ]. Scores even lower (40.43 ± 12.7) were reported for individuals with drug addiction [ 59 ].…”
Section: Discussionmentioning
confidence: 95%
“…4,8 In recent years health-related quality of life has become an important outcome, since the influence of the disease on everyday living is an important factor for the patients and assessment of health-related quality of life is essential to assess the self-perceived impact of physical and mental impairment on patient's health. 2 Quality of life (QoL) is a subjective and multidimensional index of well-being from a patient's point of view. It is defined as physical, emotional, social, mental well-being and development, activity functional ability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest report of the Global Initiative for Asthma (GINA), about 334 million people in the world have asthma. 2 Quality of life (QoL) is a subjective and multidimensional index of well-being from a patient's point of view. It is defined as physical, emotional, social, mental well-being and development, activity functional ability.…”
Section: Introductionmentioning
confidence: 99%